2019
DOI: 10.3389/fmars.2019.00560
|View full text |Cite
|
Sign up to set email alerts
|

Better Together: The Uses of Ecological and Socio-Economic Indicators With End-to-End Models in Marine Ecosystem Based Management

Abstract: Ecological and socioeconomic indicators are used as proxies for attributes of ecosystems and human communities, respectively. End-to-end models are used to predict how ecosystems will respond to alternative management actions and changing environmental conditions. Despite the importance of these two tools for Ecosystem-Based Management (EBM), there has been limited integration of ecological indicators directly into end-to-end models; the former are typically calculated post hoc with output from the latter. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 91 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…Alongside this, while ecological and environmental indicators support understanding of overarching patterns occurring within ecosystems, socioeconomic indicators are needed to help track patterns of human vulnerability and well-being (Tam et al 2019). This can aid the understanding of the complexity of the human dimensions of an EAF (Bowen and Riley 2003, Pollnac et al 2015, Colburn et al 2016, Auad et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside this, while ecological and environmental indicators support understanding of overarching patterns occurring within ecosystems, socioeconomic indicators are needed to help track patterns of human vulnerability and well-being (Tam et al 2019). This can aid the understanding of the complexity of the human dimensions of an EAF (Bowen and Riley 2003, Pollnac et al 2015, Colburn et al 2016, Auad et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A suite of socioeconomic indicators could be encompassed into this framework, helping capture the cumulative influences of fishing, environmental variability, and coastal communities on ecosystems when informing management scenarios. This will enable fisheries managers and stakeholders not only to avoid ecological regime shifts, but also undesirable shifts to human coastal communities (Tam et al 2019), providing a more holistic approach to decision making. Following some further improvements and adjustments, it is possible that this framework could be used to synthesize large amounts of information about the states and trends of marine ecosystems, in a globally comparative way.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in the case study below involving swordfish fishing closures, MSE with spatial operating models can be used to assess performance of different spatial management strategies, including those that are dynamic and environmentally informed. Ecosystem models can also test the utility of ecosystem indicators in novel decision criteria and harvest rules (Fay et al, 2015;Fulton et al, 2019;Tam et al, 2019) that extend beyond classical single species management.…”
Section: Mse Is Expanding Beyond Single Species Approaches Into Ebfm Applicationsmentioning
confidence: 99%
“…Here, we apply the LIM approach to explore the predictability of a set of fisheries time series describing the temporal changes of specific stocks. These time series can be viewed as proxies that simplify complicated biological and socioeconomic conditions over time [Blanchard et al, 2010;Tam et al, 2019]. The three fisheries databases considered in this study are (1) stock biomass anomalies from scientific stock assessments performed for a limited number of stocks in different regions (RAM database, [Ricard et al, 2012]), (2) landings of stocks as reported by the country targeting the species (LME database, [Pauly et al, 2020]), and (3) the catches of species that are estimated from data reported to the United Nations (FAO database [Pauly et al, 1998]).…”
Section: Introductionmentioning
confidence: 99%